2006
DOI: 10.1093/ejo/cji120
|View full text |Cite
|
Sign up to set email alerts
|

Are the Peer Assessment Rating Index and the Index of Treatment Complexity, Outcome, and Need suitable measures for orthognathic outcomes?

Abstract: The aim of this study was to determine which of two occlusal indices were the most appropriate for use in the assessment of orthognathic outcome. The indices used were the Peer Assessment Rating (PAR) Index and the Index of Treatment Complexity, Outcome, and Need (ICON). These indices were validated against the subjective assessments of treatment outcome and treatment improvement obtained from a panel of experienced orthodontic consultants. For the subjective assessment, intraexaminer agreement for ranking tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Studies satisfied DoE criteria when the Peer Assessment Rating Index (PAR), the index of orthodontic treatment need (IOTN), the index of orthognathic functional treatment need (IOFTN), or the index of complexity, outcome and need (ICON) were reported as the outcome measure for orthognathic surgery. The PAR is a suitable and validated clinical outcome measure for the deviation of a normal occlusion and alignment for the combined orthodontic treatment and orthognathic surgery . The IOFTN is a reliable tool for measuring patient need for orthognathic surgery and has good content validity, and good inter‐rater and moderate‐to‐good intra‐rater reliability .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies satisfied DoE criteria when the Peer Assessment Rating Index (PAR), the index of orthodontic treatment need (IOTN), the index of orthognathic functional treatment need (IOFTN), or the index of complexity, outcome and need (ICON) were reported as the outcome measure for orthognathic surgery. The PAR is a suitable and validated clinical outcome measure for the deviation of a normal occlusion and alignment for the combined orthodontic treatment and orthognathic surgery . The IOFTN is a reliable tool for measuring patient need for orthognathic surgery and has good content validity, and good inter‐rater and moderate‐to‐good intra‐rater reliability .…”
Section: Resultsmentioning
confidence: 99%
“…for orthognathic surgery. The PAR is a suitable and validated clinical outcome measure for the deviation of a normal occlusion and alignment for the combined orthodontic treatment and orthognathic surgery (22,23). The IOFTN is a reliable tool for measuring patient need for orthognathic surgery (2,24) and has good content validity, and good inter-rater and moderate-to-good intra-rater reliability (25).…”
Section: Effects Of Orthognathic Surgerymentioning
confidence: 99%
“…3 In 1990, it was estimated that there were more than 1 million potential orthognathic patients in the United States, and if this figure is applied to the UK, there may be up to one fourth of 1 million patients who would benefit from orthognathic treatment. [4][5][6] Recent Hospital Episodes Statistics data from England have suggested that the number of orthognathic surgical procedures undertaken is increasing year to year. 7 Satisfaction with outcomes of orthognathic treatment is generally high, with most studies reporting 80% to 90% of patients being happy with the result.…”
mentioning
confidence: 99%
“…1,12,13,23,24,25,26,27,28,29 Most scholars concluded that ICON could be a substitute for IOTN, Peer Assessment Rating and Dental Aesthetic Index as a good index for the prediction and evaluation of orthodontic treatment need and treatment outcome. 12,23,25,28,29,30,31 Some scholars believed that the relationship between ICON and Peer Assessment Rating needs to be studied further. 32 …”
Section: Discussionmentioning
confidence: 99%